Kostruksi Makna Tradisi Walimatul ‘Ursy bagi Masyarakat Barumanis Kabupaten Rejang Lebong, Bengkulu, Indonesia - Sutarto Sutarto; Idi Warsah; Ngadri Ngadri (UIN Sunan Gunung Djati Bandung, 2021)
The tradition of the feast of marriage or walimatul 'ursy is a Javanese tradition that can work together to motivate and become the glue of multicultural unity for the people of Barumanis village, Rejang Lebong Regency. This study aims to find and explain the meaning and experience of the Barumanis village community in carrying out the walimatul ‘ursy tradition. This research is qualitative research based on a constructivist paradigm, using a phenomenological approach. Data collection techniques through in-depth interviews, participatory observation, and data documentation. The results of the study found that there are a common understanding and belief of the community in interpreting the feast of marriage, making the wedding feast can be the glue of unity in a multicultural society. The tradition of the feast of marriage has a positive value for people's lives, therefore it is preserved by increasing community commitment and awareness, being passed down from generation to generation, and the existence of unwritten social sanctions.